Optimizing rotation lengths of major plantation species for improved wood production in southern China - Minyu Dou; Zhen Wang; Tingshuo Zhang; Zhixin Cheng; Jun Zhang; Wenzheng Fu; Markku Larjavaara; Wennong Kuang; Demeng Jiang; Fangyuan Hua (Forest Ecology and Management, 2025)

A Meta‐Regression of 18 Wildfire Chronosequences Reveals Key Environmental Drivers and Knowledge Gaps in the Boreal Nitrogen Balance - Stefan F. Hupperts; Frank Berninger; Han Y. H. Chen; Nicole Fenton; Mélanie Jean; Kajar Köster; Markku Larjavaara; Michelle C. Mack; Marie‐Charlotte Nilsson; Marjo Palviainen; Anatoly Prokushkin; Jukka Pumpanen; et al. (Global Change Biology, 2025)
Climate change has increased the size and frequency of wildfires across the boreal biome. Severe wildfires in boreal forests have been found to trigger shifts from evergreen to deciduous canopies, which has cascading effects on carbon and nitrogen cycling. Ecosystem productivity and carbon uptake in boreal forests are strongly linked with nitrogen, and Earth system models increasingly depend on our understanding of the nitrogen balance to predict post‐fire carbon uptake. To investigate the post‐fire boreal nitrogen balance, we combined a mass balance approach and literature synthesis to estimate rates of nitrogen accumulation and nitrogen inputs across a network of 18 boreal wildfire chronosequences that varied in both wildfire regime and post‐fire canopy type, comprising 527 forest stands. We found that deciduous‐ or mixed‐dominance boreal forests establishing after severe, stand‐replacing fires had the highest nitrogen accumulation rates (15.7 ± 3.8 kg ha −1 year −1 ), while evergreen‐dominated forests establishing after surface‐ or mixed‐severity fires had the lowest nitrogen accumulation rates (1.4 ± 1.1 kg ha −1 year −1 ). Annual known inputs from nitrogen deposition and biological nitrogen fixation combined, estimated from published data, largely failed to explain the rate of nitrogen accumulation, particularly in deciduous or mixed‐dominance forests establishing after stand‐replacing fires, suggesting that the origins of most nitrogen in these forest types remain poorly understood. As the frequency of severe wildfires increases across the boreal biome and shifts toward deciduous canopies become more common, our study reveals a large knowledge gap in the resulting nitrogen balance that needs to be resolved in order to improve predictions of forest carbon uptake.

Wind disturbance in forests: A bibliometric analysis and systematic review - Wen Gao; Markku Larjavaara (Forest Ecology and Management, 2024)

Climate drivers of seed rain phenology of subtropical forest communities along an elevational gradient - Liu Yang; Zehao Shen; Xuejing Wang; Shaopeng Wang; Yuyang Xie; Markku Larjavaara; Jie Zhang; Guo Li (International Journal of Biometeorology, 2023)

Comparison between the stem and leaf photosynthetic productivity in Eucalyptus urophylla plantations with different age - Xia Chen; Mingyu Luo; Yulin Kang; Ping Zhao; Zhiyao Tang; Yuanyuan Meng; Li Huang; Yanpei Guo; Xiancheng Lu; Lei Ouyang; Markku Larjavaara (Planta, 2023)

Spatio‐temporal patterns in the woodiness of flowering plants - Ao Luo; Xiaoting Xu; Yunpeng Liu; Yaoqi Li; Xiangyan Su; Yichao Li; Tong Lyu; Dimitar Dimitrov; Markku Larjavaara; Shijia Peng; Yongsheng Chen; Qinggang Wang; et al. (Global Ecology and Biogeography, 2023)
Aim Woody and herbaceous habits represent one of the most distinct contrasts among angiosperms, and the proportion of woody species in floras (i.e., “woodiness” hereafter) represents a fundamental structural element of plant diversity. Despite its core influence on ecosystem processes, spatio‐temporal patterns in woodiness remain poorly understood. Here, we aim to demonstrate the global spatio‐temporal patterns in angiosperm woodiness and their relationship with environmental factors. Location Global. Time period Cenozoic, 66 Ma to present. Major taxa studied Angiosperms. Methods Using newly compiled data on the growth forms and distributions of c . 300,000 angiosperm species and an angiosperm phylogeny, we mapped the current global geographical patterns in angiosperm woodiness, reconstructed ancestral states of growth forms through the angiosperm phylogeny and demonstrated the Cenozoic evolutionary dynamics of woodiness. We evaluated the relationships between woodiness and current climate and palaeoclimate. Results We found that c . 42.7% of angiosperms are woody. Woodiness decreased spatially from the equator towards high latitudes, temporally since the early Cenozoic. Temperature was the best predictor of the spatio‐temporal decline in woodiness and was positively correlated with woodiness. Despite the temporal decline in woodiness, macroevolutionary herbaceous‐to‐woody transitions increased through time and contributed to the evolution of woody floras in temperate drylands, whereas the opposite transitions decreased through time and contributed to herbaceous floras in tropical and subtropical drylands. Main conclusions Our study improves understanding of the spatio‐temporal dynamics of angiosperm woodiness. Our findings suggest that temperature is likely to be a determinant of spatio‐temporal variations in woodiness, highlighting the role of temperature in maintaining the growth form composition of ecosystems. Our study also calls for attention to growth form transitions (e.g., secondary woodiness) in temperate drylands that have been neglected before.

Wind and gravity in shaping Picea trunks - Markku Larjavaara; Mikko Auvinen; Anu Kantola; Annikki Mäkelä (Trees, 2021)

Dead Wood Necromass in a Moist Tropical Forest: Stocks, Fluxes, and Spatiotemporal Variability - Evan M. Gora; Riley C. Kneale; Markku Larjavaara; Helene C. Muller-Landau (Ecosystems, 2019)

Temperature explains global variation in biomass among humid old‐growth forests - Markku Larjavaara; Helene C. Muller‐Landau (Global Ecology and Biogeography, 2012)
Aim To develop and test a simple climate‐based ecophysiological model of above‐ground biomass – an approach that can be applied directly to predicting the effects of climate change on forest carbon stores. Location Humid lowland forests world‐wide. Methods We developed a new approach to modelling the aboveground biomass of old‐growth forest (AGB max ) based on the influences of temperature on gross primary productivity (GPP) and what we call total maintenance cost (TMC), which includes autotrophic respiration as well as leaf, stem and other plant construction required to maintain biomass. We parameterized the models with measured carbon fluxes and tested them by comparing predicted AGB max with measured AGB for another 109 old‐growth sites. Results Our models explained 57% of the variation in GPP across 95 sites and 79% of the variation in TMC across 17 sites. According to the best‐fit models, the ratio of GPP to maintenance cost per unit biomass (MCB) peaks at 16.5 °C, indicating that this is the air temperature leading to the highest possible AGB max when temperatures are constant. Seasonal temperature variation generally reduces predicted AGB max , and thus maritime temperate climates are predicted to have the highest AGB max . The shift in temperatures from temperate maritime to tropical climates increases MCB more than GPP, and thus decreases AGB max . Overall, our model explains exactly 50% of the variation in AGB among humid lowland old‐growth forests. Main conclusions Temperature plays an important role in explaining global variation in biomass among humid lowland old‐growth forests, a role that can be understood in terms of the dual effects of temperature on GPP and TMC. Our simple model captures these influences, and could be an important tool for predicting the effects of climate change on forest carbon stores.